EDUCATION FOR HEALTH PROMOTION OF AN ARTERIAL HIPERTENSIVE GROUP - Mercedes Trentini; Neusi Tomasi; Ymiracy Polak (Universidade Federal do Paraná, 1996)
This practice research on health promotion was carried out with a group of persons with arterial hypertension in Curitiba, Paraná. The conceptual framework was constructed by the following concepts: health promotion, health education, and coping. The data were obtained during meetings wich were carried out each days during one year period. The finding showed relationships between stressors, stress, emotions and arterial hipertention. The main stressors were: financial conditions, work conditions, health care, family relationships and losses. The health promotion ocurred through a coping task teaching-learnig process.